2013
DOI: 10.1515/hf-2012-0193
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate (POM)-aided modification of lignin from wheat straw biorefinery

Abstract: Abstract:The oxidative modification of Biolignin (BL) has been investigated to make it more suitable as an adsorbent for transition/heavy metals. BL is a by-product of a wheat straw organosolv process for the production of pulp, ethanol, and pentoses (CIMV S.A. pilot plant, Levallois Perret, France). It was subjected to oxidation by a polyoxometalate (POM) H 3 [PMo 12 O 40 ], aiming at the increment of oxygen-containing adsorption-active sites. The POM oxidation of BL was performed under moderate conditions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 35 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…These changes indicated that -OH and -COOH were involved in the adsorption process [46,47]. Generally, the -OH of lignin linkages with cations groups through electrostatic attractions or surface exchanges, while the -COOH groups were ionized as -COO − groups at higher pH, and provided potential sites for coordinative linkages with cations groups [38,40,48]. Based on these results, the enhanced adsorption capacity of PHPLs on MB can be greatly attributed to the increased -OH and -COOH on the surfaces of PHPLs, which was mainly resulted from the oxidative modification in the pretreatment.…”
Section: Adsorption Of Cationic Substances By Phplsmentioning
confidence: 99%
See 3 more Smart Citations
“…These changes indicated that -OH and -COOH were involved in the adsorption process [46,47]. Generally, the -OH of lignin linkages with cations groups through electrostatic attractions or surface exchanges, while the -COOH groups were ionized as -COO − groups at higher pH, and provided potential sites for coordinative linkages with cations groups [38,40,48]. Based on these results, the enhanced adsorption capacity of PHPLs on MB can be greatly attributed to the increased -OH and -COOH on the surfaces of PHPLs, which was mainly resulted from the oxidative modification in the pretreatment.…”
Section: Adsorption Of Cationic Substances By Phplsmentioning
confidence: 99%
“…The degree of modification on lignin can be control by changing the addition of H 2 O 2 input. The resultant PHP lignin has abundant oxygen-containing functional groups, and can potentially work as a functional adsorbent to remove some cationic substances from aqueous solution [17,38].…”
Section: Lignin Modification During Php Pretreatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The first category is oxygen-containing functional groups where acid treatment increases the naturally occurring fraction of oxygen groups as well as the hydrophobicity of the lignins. This process can significantly increase the adsorption rates for metals such as Cd and Pb ( [95], Table 9) provided the pH is also controlled. In general, oxidised lignins have been shown to exhibit stronger adsorption capabilities than unmodified lignins due to the higher amounts of carboxyl groups present [96].…”
Section: Modification Of Lignins To Enhance Adsorptionmentioning
confidence: 99%